Advanced practice nurses' experiences of evidence-based practice: A qualitative study. (December 2022) - Ylimäki, Saija; Oikarinen, Anne; Kääriäinen, Maria; Holopainen, Arja; Oikarainen, Ashlee; Pölkki, Tarja; Meriläinen, Merja; Lukkarila, Pirjo; Taam-Ukkonen, Minna; Tuomikoski, Anna-Maria
Evidence-based practice (EBP) has been shown to improve patient safety as well as quality of care. Advanced practice nurses (APNs) have a vital role in the implementation of EBP. This study aimed to describe APNs' experiences of EBP implementation. The study was a descriptive qualitative study and data were collected between May and August 2019 through interviews with APNs ( n = 12). The data were analyzed using inductive content analysis. The study was reported according to COREQ guidelines. The responses were divided into four main categories: EBP in clinical nursing; EBP leadership; implementation of supporting structures for EBP; and EBP in APNs' work. APNs experienced: that the realization of EBP varied in clinical nursing, that there was a need for development in the leadership of EBP, variation in nurse leaders' competence in EBP leadership, and a lack of resources for EBP.